Extrapolation of Punctual Data of Ablation Concerning the Whole Strandline Glacier through the Analysis of the Influence of Climate Factors - MOTTA, Michele (2008)
The results show the goodness of the choice of integration between the ablation data and a model of distribution of the ablation factors (e.g. insolation). The ablation data, than in the traditional method are useful only as punctual statistical indicators, become the basis of a mass balance of high accuracy. This method is suitable for all the mass balances established by climatic factors, especially for the glaciers partially inaccessible. Besides, the method can be useful for completing “holes” in the series of ablation data, when a continuous recording of radiation data is available.